Verifikasi Dan Kalibrasi Model Matematis Aliran Permukaan Dua Dimensi (Rma2), Pengaruh Eddy Viscosity Dan Kekasaran Dasar Pada Pola Aliran - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The development of numerical models has provided some potentially useful engineering softwares especially for hydraulic engineering. A software called RMA2 in the BOSS SMS package is one of them that were supposed to be able to simulate 2D depth averaged surface water flow. A study has been conducted to verb the performance of the RMA2 software on flow influenced by tidal backwaters. The verification was done by comparing the result of flow simulation of dynamic backwater flow on a sinuous channel with a narrow section and the measured data on a physical model of flow on the same system. The measurement of flow velocity and flow pattern implemented particle image velocimetty method by using foam/patched floating tracer. Flow velocity data on several flow measurement stations were analysed quantitatively and the flow patterns were discussed qualitatively. The result of the study shows that the curves of velocity magnitudes on all measurement measured from the physical model and simulated by the mathematical model have very small differences. This result was achieved by implementing several zones in the computational domain with different roughness and diffusion coefficients. Both the mathematical and physical model shows similar pattern.